Consumption habits of “Free range chicken” in Hungary - Tikász, Ildikó Edit; Szűcs, István; Stündl, László (Applied Studies in Agribusiness and Commerce, 2009)
Poultry is highly ranked in theWorld meat production and consumption (it accounted for 32% in 2007), and, in the past 20 years it was growing with an annual rate of 3–6%, higher than in case of any other meat-types. This tendency is also valid for Hungary: poultry has the largest share (29.8 kg/person/year, 47%) in the domestic meat consumption since 2000, which is among the EU top (KSH, 2007). As the result of the animal health and nutrition scandals, the EU animal welfare and quality requirements and the advancements in health consciousness the Master-Good group launched the production, processing and trade of free-range poultry under the brand “Free-range chicken”. The new products had good consumer responses, because at present 1.5% of the processed chicken in Hungary (25 tons/week) is under this brand. As it regards the future of this product, we can expect the decrease of the current 1.5 times higher production price over broiler chicken, due to the increasing energy, labour and other cost items, thus the increase of the domestic consumption by 25–30% per annum can be foreseen. Besides the growth in domestic demand, increasing foreign consumer demand can also be expected because of the space requirement of the production. Summarising the above mentioned: „Free range chicken” can be one of the most successful products of the Hungarian poultry industry. In order to realise the prognosis mentioned above, it is inevitable to learn the consumer attitudes towards the brand. A primary market research programme supported by the Master Good group has been launched to study the main features of the domestic chicken meat consumption – including the „Free-range chicken” as highlighted brand. The primary aim of the research was the complete assessment and evaluation of the Hungarian chicken consumption habits and the identification of the possible take-off points. The research undertaken resulted basic information concerning the internal structure of the Hungarian poultry consumption (including that of the „Free-range chicken”), the potential consumer groups and their requirements, provided information on the consumers’knowledge of the products and identified the elements of the consumers’ judgements. This will serve as basis for a marketing communication programme to increase the domestic „Free-range chicken” consumption.